2003
DOI: 10.1074/jbc.m305305200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Male Determinant Factor for Brassica Self-incompatibility

Abstract: Many flowering plants possess a self-incompatibility system to prevent inbreeding. In Brassica rapa, self/ non-self recognition in mating is established through S-haplotype-specific interactions between stigma receptors and S-locus protein 11 (SP11, also called S-locus cysteine-rich protein) that is encoded at the highly polymorphic S-locus. Here we describe the solution structure of the SP11 protein of the S 8 -haplotype (S 8 -SP11), which specifically binds to the stigma factor of the same haplotype. It fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 42 publications
0
43
0
2
Order By: Relevance
“…Tyr52, which is conserved in many Brassica SCRs (Supplementary information, Figure S3A), is sandwiched between the α-helix and the β-sheet (Supplementary information, Figure S3B), and this configuration may also contribute to the structural integrity of SCR9. Database searches revealed that the structure of SCR9 is similar to the structures of SCR8 [22], plant defensins [28], and scorpion neurotoxins [29] (Figure 3C), though the positions of their disulfides bonds are not conserved. Despite this high level of structural similarity, these proteins exhibit strikingly different surfaces (Supplementary information, Figure S3C), which may allow them to have different mechanisms of action and biological activities.…”
Section: The Structure Of Scr9mentioning
confidence: 99%
See 1 more Smart Citation
“…Tyr52, which is conserved in many Brassica SCRs (Supplementary information, Figure S3A), is sandwiched between the α-helix and the β-sheet (Supplementary information, Figure S3B), and this configuration may also contribute to the structural integrity of SCR9. Database searches revealed that the structure of SCR9 is similar to the structures of SCR8 [22], plant defensins [28], and scorpion neurotoxins [29] (Figure 3C), though the positions of their disulfides bonds are not conserved. Despite this high level of structural similarity, these proteins exhibit strikingly different surfaces (Supplementary information, Figure S3C), which may allow them to have different mechanisms of action and biological activities.…”
Section: The Structure Of Scr9mentioning
confidence: 99%
“…But whether these regions are generally required for the recognition of all SCRs by their cognate SRKs remains unknown. In the case of SCR variants, which are more polymorphic than SRKs, an NMR study suggested that these small proteins of ~50 amino acids that typically contain eight conserved cysteines may all have a structure similar to defensins [22]. One study of two B. oleracea SCR variants, SCR6 and SCR13, showed that four contiguous amino-acid residues located between the fifth and sixth conserved cysteines are critical for the specific recognition of SCR13 by SRK13 but not for the recognition of SCR6 by SRK6 in planta [23].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that other regions of RsSP11-6 may also be important for the recognition by the BoS-18 stigmas. Mishima et al (2003) have elucidated the solution structure of the SP11 proteins, in which Region III forms an a-helix and Region V corresponds to the region from b2 to b3. Region III and Region V are arranged close to each other by disulfide linkage (Takayama et al, 2001;Mishima et al, 2003).…”
Section: Regions Of Sp11 Important For the Recognition By Srkmentioning
confidence: 99%
“…Mishima et al (2003) have elucidated the solution structure of the SP11 proteins, in which Region III forms an a-helix and Region V corresponds to the region from b2 to b3. Region III and Region V are arranged close to each other by disulfide linkage (Takayama et al, 2001;Mishima et al, 2003). The lower half of Boxes indicate the conserved Cys residues, and asterisks show the same amino acid residues between two sequences.…”
Section: Regions Of Sp11 Important For the Recognition By Srkmentioning
confidence: 99%
See 1 more Smart Citation